1998
DOI: 10.1172/jci2834
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of thymic tissue in adults with human immunodeficiency virus-1 infection.

Abstract: The thymus in adults infected with the HIV-1 is generally thought to be inactive, both because of age-related involution and viral destruction. We have revisited the question of thymic function in adults, using chest-computed tomography (CT) to measure thymic tissue in HIV-1-seropositive ( n ϭ 99) or HIV-1-seronegative ( n ϭ 32) subjects, and correlating these results with the level of circulating CD4 ϩ and CD8 ϩ T cells that are phenotypically described as naive thymic emigrants. Abundant thymic tissue was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
149
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 53 publications
9
149
0
2
Order By: Relevance
“…Using this approach, McCunne et al . [10] found abundant thymic tissue measured by a CT slice in half of the untreated adult HIV-1 infected patients over 39 years old. This same group observed that the evolution of naïve T-cells during the follow up was associated with larger thymuses at the end of the treatment period [11].…”
Section: Introductionmentioning
confidence: 90%
“…Using this approach, McCunne et al . [10] found abundant thymic tissue measured by a CT slice in half of the untreated adult HIV-1 infected patients over 39 years old. This same group observed that the evolution of naïve T-cells during the follow up was associated with larger thymuses at the end of the treatment period [11].…”
Section: Introductionmentioning
confidence: 90%
“…This is the "limited renewal" scenario. 8,10,11,16,35,44 The two scenarios differ in the mechanism for disease progression, and in the relevance of therapies aiming at immune reconstitution. In the limited renewal scenario disease progression is due to insufficient production in the CD4 1 T cell com partment, whereas in the proliferative exhaustion scenario it is the highly stressed homeostatic response that causes the regenerative capacity to ultimately, and irreversibly, burn out.…”
Section: Normal Telomere Lengths In Hiv-1 Infectionmentioning
confidence: 99%
“…The interest in human thymic function in the elderly has increased after studies showed that (1) the adult thymus of HIV-infected patients without treatment (McCune et al 1998) or under highly active antiretroviral therapy (HAART) (Franco et al 2002;De la Rosa and Leal 2003) maintained or even improved its function, actively contributing to the CD4 lymphocyte repopulation; (2) adult thymopoiesis can be increased with growth hormone administration (Goldberg et al 2007) or pharmacological androgenic blockade (Sutherland et al 2005;Goldberg et al 2007b). Therefore, the capacity of effectively reversing, at least partially, the thymic atrophy opens up new perspectives in order to delay the immunosenescence process.…”
Section: Introductionmentioning
confidence: 99%